Age at Menarche and Menopause, Reproductive Lifespan, and Risk of Cardiovascular Events Among Chinese Postmenopausal Women: Results From a Large National Representative Cohort Study - Chen, Lu; Hu, Zhen; Wang, Xin; Song, Yuxin; Chen, Zuo; Zhang, Linfeng; Zheng, Congyi; Vallis, Jillian; Zhou, Haoqi; Cao, Xue; Tian, Yixin; Cai, Jiayin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background At present, the association between age at menarche and menopause, reproductive lifespan, and cardiovascular disease (CVD) risk among Chinese postmenopausal women is not clear, and some related researches are contradictory. Methods A total of 6,198 Chinese postmenopausal women with a mean age of 63.6 years were enrolled at baseline in 2012–2015 and followed up for 5 years. A standardized questionnaire was used to collect relevant information by well-trained interviewers. Physical examination of the participants was performed by trained medical staff. CVD events were observed during follow-up. Cox proportional hazards models were used to estimate hazard ratios between reproductive characteristics and CVD events. Results Age at menarche was positively associated with CVD events (HR, 1.106; 95%CI, 1.047–1.167). There was a negative association between age at menopause and CVD risk in postmenopausal women with comorbidity (HR, 0.952; 95%CI, 0.909–0.996). Reproductive lifespan was negatively associated with CVD events (HR, 0.938; 95%CI, 0.880–0.999). The CVD risk increased by 10.6% for every 1-year increase in age at menarche. The CVD risk reduced by 6.2% for every 1-year increase in age at menopause in women with comorbidity. The CVD risk reduced by 3.8% for every 1-year increase in reproductive lifespan. Conclusions Based on the large prospective study with a nationally representative sample, Chinese postmenopausal women with late age at menarche and shorter reproductive lifespan have higher risk of CVD events.